Alleviation of poverty among OIC countries through sadaqat, cash waqf and public funding - Amuda, Yusuff Jelili; Che Embi, Nor Azizan (International Association of Computer Science and Information Technology (I A C S I T), 2013)

(untitled)
This paper discusses the design of an efficient and optimal cooperation and unity among OIC countries for the integration of waqf properties and sadaqat and public funding as a viable instrument to alleviate poverty rate among Muslims globally. Poverty is rampant and common among Muslims globally and their financial constraints call for urgent, collective and concrete efforts among OIC countries to improve the conditions of poor Muslims regardless of their colour, gender, nationality, and sect since Islam simplifies unity. The study analyses the types and nature of investment that can be invested in with integrated charities such as waqf properties, sadaqat and public funding to create employment in order to reduce the poverty rate in concerned and targeted nation. It will further analyze how the financial status of Muslims can be improved.